Problems of adiabatic quantum program design - Khusnitdinova, Evgeniya. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Although several quantum programming languages have already been proposed, none of these are based on the newly discovered adiabatic evolution approach. We acknowledge the main problem in adiabatic quantum computation to be the lack of insight that common programmers have about the design of Hamiltonians. In the present work we provide necessary background in physics and algebra and the basics of adiabatic quantum computation with comprehensive discussion of both examples seen in literature and new ones. We examine some flow control constructs like loops and branching from the adiabatic quantum perspective to illustrate the main design problems as a first step towards the development of an adiabatic quantum programming infrastructure.
Keywords: Mathematical physics.